Women and domestic violence in Bangladesh: seeking a way out of the cage - Ashrafun, Laila (Routledge/Asian Studies Association of Australia (ASAA) South Asian series, 2018)
Introduction -- Methodological choice -- The girlhood and marriage: perceptions and experiences of slum women -- Liberating own space: in quest of self-identity and agency in everyday life -- Women's married life and domestic violence in the slum -- Unveiling domestic violence from the privacy of home -- Legal battles at the counseling center: what do the women get? -- Conclusions